The Principle of Politeness in the English and Uzbek Languages (Eurasian Research Bulletin, 2022)
Politeness is the practical application of good manners or etiquette so as not to offend others. It is a culturally defined phenomenon, and therefore what is considered polite in one culture can sometimes be quite rude or simply eccentric in another cultural context. While the goal of politeness is to refrain from behaving in an offensive way so as not to offend others and make all people feel relaxed and comfortable with one another, these culturally defined standards at times may be manipulated. The relevance of the study is due to the growing interest of linguists in the problems of interpersonal verbal interaction and the psychology of speech behavior of native speakers. Much attention is paid to the study of speech etiquette, the functioning of conventional phrases and the degree of their clichés, especially in cultural and comparative terms. However, these aspects are only the essence of explicit or conventional politeness (R. Ratmayr). Implicit or individual politeness, consisting in respecting the maxim of politeness, implemented by various strategies of courtesy and diplomacy, has not been studied enough and, undoubtedly, should be the object of closer attention of linguists